PENGARUH PROGRAM PEMBERDAYAAN USAHA GARAM RAKYAT (PUGAR) TERHADAP KAPITAL SOSIAL PETAMBAK GARAM DI DESA TASIKHARJO KECAMATAN KALIORI KABUPATEN REMBANG PROVINSI JAWA TENGAH - Zaka Lawang, Robert Markus; Nisa, Putri Khoiron (Istek Widuri Jakarta, 2019)
Empowerment (PUGAR) program on the social capital of salt farmers in Tasikharjo village Capacity of social groups to act in their collective interest depends on the institusional based development policy. The purpose of this research is to measure the influence of the People’s Salt Business, Kaliori district, Rembang regency, Central Java Province. The aproach used in this research is quantitative. The data analysis technique used simple linear regression and T test. The results shows that the PUGAR program influence the social capital of salt farmers by 39.1% while 60.9% was influenced by other factors. The relationship between PUGAR program and social capital is in a strong category with a coefficient (R) of 0.625. The results of the T test shows PUGAR program has a positive effect on social capital which can be seen from the regression coefficient of the PUGAR program variable of 0.598 has positive value. The PUGAR program has a significant effect on social capital with a confidence level of 95%, and a value of α = 0.05 which can be seen as tcount> ttable (4,624> 2,039513).